EEASA 2004 Keynote Address - Environment as Life:The Journey of an Environmental Educator - Danie Schreuder (Environmental Association of Southern Africa, 2004)
In this paper I discuss the constructs environment and human existence in terms of the lessons I have learnt from biological life processes. I draw on personal experiences in my journey as an educator and the influences that local, international and global changes in environmental education have had on my practice and on my understanding of key concepts. I link the development of some of my critical understandings to my personal, lived experiences as a biology teacher in times of political turmoil and change in South Africa. I argue that the development of my key understanding of both environment and education is rooted in my experiences and encounters in the natural world and that, for me, environmental education processes are about appreciating, celebrating and preserving life and the place where life is possible, thereby helping people to become inhabitants and not merely residents. Environmental education is a critical pedagogy that should focus on and critically expose practices, ideologies and hegemonies that oppress and undermine people and their thinking and, in effect, threaten not only the quality of human life, but also the capacity of the earth to sustain life.